Receptor–ligand and parasite protein–protein interactions in Plasmodium vivax: Analysing rhoptry neck proteins 2 and 4 (2018)
Elucidating receptor–ligand and protein–protein interactions represents an attractive alternative for designing effective Plasmodium vivax control methods. This article describes the ability of P. vivax rhoptry neck proteins 2 and 4 (RON2 and RON4) to bind to human reticulocytes. Biochemical and cellular studies have shown that two PvRON2- and PvRON4-derived conserved regions specifically interact with protein receptors on reticulocytes marked by the CD71 surface transferrin receptor. Mapping each protein fragment's binding region led to defining the specific participation of two 20 amino acid-long regions selectively competing for PvRON2 and PvRON4 binding to reticulocytes. Binary interactions between PvRON2 (ligand) and other parasite proteins, such as PvRON4, PvRON5, and apical membrane antigen 1 (AMA1), were evaluated and characterised by surface plasmon resonance. The results revealed that both PvRON2 cysteine-rich regions strongly interact with PvAMA1 Domains II and III (equilibrium constants in the nanomolar range) and at a lower extent with the complete PvAMA1 ectodomain and Domains I and II. These results strongly support that these proteins participate in P. vivax's complex invasion process, thus providing new pertinent targets for blocking P. vivax merozoites' specific entry to their target cells. © 2018 John Wiley and Sons Ltd